Spatiotemporal Measurement of Charge at Ceramic Substrate-Silicone Gel Interface in Medium-Voltage Power Modules - Li, Kaixuan; Zhang, Boya; Yang, Ziyue; Jiang, Xinyu; Yao, Minghan; Li, Xingwen (IEEE transactions on power electronics, 2024)
With the proliferation of high-voltage, high-power density devices, insulation failure has emerged as a latent hazard in power modules. Notably, breakdown along ceramic substrate-silicone gel interfaces is a typical insulation failure process in power modules, necessitating particular attention and elucidation. Specifically, the charge movement characteristics that play a pivotal role in the failure process should be expounded. However, the lack of characterization methods currently renders these characteristics unclear. In this study, we proposed a method for the spatiotemporal measurement of the interfacial charge density between a direct-bonded copper ceramic and silicone gel. A reflective optical system was developed based on the Pockels effect to enable the measurement of nontransparent samples, such as encapsulation structures, in power modules. The measurement range of the optical system is ±20 kV. The interfacial charge density was calculated using an inversion algorithm. Charge dynamics at inaccessible interfaces were described for the first time. The threshold is ∼100 pC/mm 2 with 10- μ s temporal and 27- μ m spatial resolution. Compared with traditional methods, the proposed method stands out for its superior spatiotemporal dimensionality. Besides, it enables visual measurements, making it a solution for monitoring insulation status and diagnosing insulation defects specifically for encapsulation structures in power modules. The proposed method can help engineers improve the insulation design of power modules. This article is accompanied by a video demonstrating the dynamic process of discharge.